2012
DOI: 10.1021/np200919a
|View full text |Cite
|
Sign up to set email alerts
|

Carbazole Alkaloids from the Stems of Clausena lansium

Abstract: Ten new carbazole alkaloids, claulansines A−J (1−10), and seven known analogues (11−17) were isolated from the stems of Clausena lansium. Their structures were established on the basis of extensive spectroscopic analyses, and their absolute configurations were determined by CD experiments and computational methods. Screening results indicated that compounds 1, 6, 8−10, 13, 14, and 17 showed selective neuroprotective effects at the concentration of 10 μM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
60
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 84 publications
(63 citation statements)
references
References 14 publications
3
60
0
Order By: Relevance
“…Analyses of the NMR spectra indicated that 3 was also a 1-oxygenated 2,3-substituted carbazole alkaloid, similar to the known compound claulansine E [2].…”
Section: Accepted Manuscriptmentioning
confidence: 72%
See 1 more Smart Citation
“…Analyses of the NMR spectra indicated that 3 was also a 1-oxygenated 2,3-substituted carbazole alkaloid, similar to the known compound claulansine E [2].…”
Section: Accepted Manuscriptmentioning
confidence: 72%
“…The nineteen known carbazole alkaloids were identified to be mafaicheenamine C (6) [12], mafaicheenamine E (7) [13], claulansine G (8) [2], claulamine E (9) [14],…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The known compounds isolated were claulansine B (4b), 10 claulansine D (5b), 10 (À)-(1S,3S)-1-methyl-1,2,3,4-tetrahydro-b-carboline-3-carboxylic acid (6a), 28 (+)-(1R,3S)-1-methyl-1,2,3,4-tetrahydro-b-carboline-3-carboxylic acid (6b), 28 (R)-isoplatydesmine (7a), 29 (S)-isoplatydesmine (7b), 30 claulansine A (8), 10 ribalinine (9), 31 g-fagarine (10), 32 dictamnine (11), 33 N-(2-hydroxy-2-phenylethyl)-cinnamamide (12), 34 N-phenylethylbenzamide (13).…”
Section: Resultsmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10] The leaves and fruits of Clausena lansium, Clausena excavata, Clausena emarginata, and Clausena anisum-molens are not only eaten as food but also used for traditional medicine.…”
mentioning
confidence: 99%
See 1 more Smart Citation